Delivery of Personalized Care for Locally Advanced Rectal Cancer: Incorporating Pathological, Molecular Genetic, and Immunological Biomarkers Into the Multimodal Paradigm - Ryan, Éanna J.; Creavin, Ben; Sheahan, Kieran (Frontiers in Oncology, 2020)
Approximately one-third of all newly diagnosed CRC is comprised of rectal cancer and the incidence has been rising among younger patients. The principal neoadjuvant treatments are neoadjuvant short-course RT and long-course chemoradiation (nCRT). Locally advanced rectal cancer (LARC) is particularly challenging to manage given the anatomical constrictions of the pelvis and the risk for local recurrence. In appropriately treated patients, 5-year and 10-year overall survival is estimated at 60% and 50%. The prognosis for LARC has improved in recent years with more access to screening, advances in surgical technique and perioperative care, and the refinement of the multidisciplinary team with combined-modality management strategies. These advanced have been augmented by significant improvements in the understanding of the underlying tumour biology. However, there are many patients whose outcomes do not match those typical for their tumour stage and accurate prognostic information for individual patients can be difficult to estimate due to the heterogeneous nature of LARC. Many new combinations of chemotherapy with radiotherapy, including total neoadjuvant therapy with targeted therapies that aim to reduce toxicity and increase overall are undergoing evaluation in clinical trials. Despite these advances, the rates of local recurrence and distant metastasis remain a cause for concern: one-third of patients with LARC will die within 5 years of completion of treatment. While much of the new pathological, molecular genetic, and immunological biomarkers allows refinement in the classification and prognostication of CRC the relative importance of each of these factors with regards to the development and progression of LARC remains incompletely understood. These factors are often insufficiently validated and rarely consider the individual characteristics of the patient, the tumour and its location, the local available expertise or the expected site of recurrence. Understanding the mechanisms behind these discrepancies will allow for a more precise, personalised approach, better informed treatment options, and ultimately improved outcomes. This review aims to first outline the current multidisciplinary context in which LARC care should be delivered and then discuss how some key prognosticators, including novel histopathological, molecular genetic and immunological biomarkers, might fit into the wider context of personalised LARC management in the coming years.